2012
DOI: 10.1002/cctc.201200482
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of Zeolite‐Supported Vanadia in the Aerobic Oxidation of 5‐hydroxymethylfurfural to 2,5‐diformylfuran

Abstract: The catalytic performance of zeolite‐supported vanadia catalysts was examined for the aerobic oxidation of 5‐hydroxymethylfurfural (HMF) to 2,5‐diformylfuran (DFF) in organic solvents such as N,N‐dimethylformamide (DMF), methyl isobutyl ketone, toluene, trifluorotoluene and DMSO. Catalysts based on the four different zeolite supports H‐beta, H‐Y, H‐mordenite, and H‐ZSM‐5 with 1–10 wt % vanadia loading were prepared and characterized by nitrogen physisorption, X‐ray powder diffraction, scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 40 publications
3
92
0
1
Order By: Relevance
“…But higher extent of leaching was found at higher pressures. 91 This is a good indication that the parameters 20 of the reaction have a great impact on the stability of the catalyst.…”
Section: Coping With the Leachingmentioning
confidence: 94%
“…But higher extent of leaching was found at higher pressures. 91 This is a good indication that the parameters 20 of the reaction have a great impact on the stability of the catalyst.…”
Section: Coping With the Leachingmentioning
confidence: 94%
“…13 Magnetic nanoparticles have great potential in view of their easy recovery and accessibility, and can be prepared…”
Section: Scheme 1: Structures Of Amides and Phosphoroamidatesmentioning
confidence: 99%
“…Therefore, great effect has been devoted to the design of non-noble metal based heterogeneous catalysts for the oxidation of HMF into DFF. There were some non-noble metal based heterogeneous catalysts reported for the oxidation of HMF into DFF such as Mo-containing keggin heteropolyacids [19], vanadium-containing catalyst [20] and manganese oxide catalysts [21]. However, some of them showed low catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of them showed low catalytic activity and stability. For example, Sádaba, et al [20] reported that a reaction selectivity towards DFF of > 99% at 84% HMF conversion was obtained by the use of 1 wt% V 2 O 5 /H-beta as the catalyst. However, the catalytic activity lost seriously in the second run due to the loss of the active sites.…”
Section: Introductionmentioning
confidence: 99%